STUDI ANALISIS RAPID APLICATION DEVELOPMENT SEBAGAI SALAH SATU ALTERNATIF METODE PENGEMBANGAN PERANGKAT LUNAK - Noertjahyana, Agustinus (Institute of Research and Community Outreach - Petra Christian University, 2002)
Rapid Application Development is one of the alternatives of System Development Life Cycle which is lately used to cope with the